Bibliometric Analysis of Herbal Used for Diabetic Food Ulcer - Pratiwi, Sekar Ayu; Hertiani, Triana (Majalah Farmaseutik, 2024)
Diabetic Foot Ulcer (DFU) is a serious condition prevalent among diabetic patients. Due to its minimal side effects and cost-effectiveness, herbal remedies have garnered attention for DFU treatment. Many researchers are exploring effective herbal treatments. Bibliometric analysis serves as a tool to understand research focus and trends and identify extensively studied or underexplored herbs. In this study, publications related to herbal treatments for DFU were obtained from the Scopus database, where 90 articles meeting the inclusion criteria were analyzed using Vosviewer 1.6.20 software. The analysis was conducted using co-occurrence methods on titles and abstracts to provide an overview of herbal research for DFU, while co-occurrence methods on keywords offer a more detailed focus. Based on keyword analysis, the most frequently cited herb in the 90 articles over the past 10 years is Aloe Vera. Meanwhile, the analysis of titles and abstracts indicates that the most cited terms are "Angiogenesis," "Ointment," and "Infection." The findings of this study are expected to guide researchers in further exploring the potential of herbal treatments for DFU, thus contributing to the development of more effective and efficient therapies for diabetic patients suffering from foot ulcers.